Location approach in integrating the hub and the gateway building and maximizing the built-up area's potentials affected by the impact of transportation system's geography - Banayo, Maratriz C. (2010)
Davao City Overland Transportation Terminal is presently located at one of the built-up areas in the city. The terminal was proposed to be situated in some part of the Diversion Road. The reason for relocating the facility was due to the proliferation of transportation issues on urban built-up area, such for instance was the congestion of people and automobiles around the existing terminal location. The system of repositioning the terminal facility is the mathematical calculation of the traffic distribution among the two given locations, namely, at Ecoland (terminal's existing location) & Diversion Road ( the proposed terminal location). The method used is the Gini Coefficient location approach (Chapter V). The impact of the location method in this particular study was basically, to provide and show the difference of the concentration in the given locations. The lesser the traffic concentration of a location, the advantageous it is for a terminal spot. Gini Coefficient in this case, reaps off the advantage of location with lesser traffic distribution. Another importance of the terminal's relocation was it's another way of extending one of the legs of urban sprawl out of the inner city spaces. Urban sprawl is a healthy form of urban development for the city considering the land area of Davao. It favors outer city development. Relocating the terminal facility outside the main city belt, enables inner city roads to only cater inter-modal transportation means and some private vehicles that may include cargo trucks for any private business purposes. In addition, the proposed terminal location will open routes for jeepneys which will serve commuters going to and from the terminal facility to the city proper. Moreover, in order to provide a suitable terminal facility to the users, the research went through space programming. The study area was the relationships among the existing terminal spaces. These relationships were further adapted into the new terminal spaces in terms of space adjacency and new approaches in space planning. Modification were done in order to suit the design concept presented in the translation part of the study ( Chapter X).